Construção de reator de plasma frio para aplicações de filmes finos - Pinto, Henrique Moreira (Universidade Federal de São Carlos, 2022)
It is about the construction of a sputtering system, through the use of a cold plasma reactor, for the deposition of metallic thin films. Basically, this system works by ejecting atoms from a material (target) by the bombardment of argon ions. This process occurs through the ionization of Argon gas, which has its ions accelerated towards the target and when they collide with the material, ejection occurs, and these separate atoms are deposited on the substrate, forming a thin film of this material. The process for applying metallic thin films through sputtering is used in several areas, such as industrial use, for beautifying and coating parts, food packaging, jewelry, photovoltaic applications and academic research. The construction was made with components found on the market, taken from other electronic equipment, vacuum system and machined parts. The use of this experience can be applied in several areas, and the object of study for this case is to characterize the deposition equipment through the relationship between the thickness of the deposited thin film and deposition time. In addition, the ohmic resistance and the uniformity rate of the deposited material (relationship thickness and distance from the center of the anode) were also characterized. Due to the characterization of the equipment, several other characterizations can be made, such as through analysis of the purity and structure of the generated film, in addition to comparing the equipment in terms of deposition rate and others of interest, being able to use it by laboratories within and outside the University, because the rack that holds the reactor, despite being robust, has wheels at its base, allowing it to be transported with care.
Construction of cold plasma reactor for thin film applications
Keywords: Bombardeamento iônico; Filmes finos metálicos; Pulverização catódica; Reator de plasma frio; Sputtering; Ion bombardment; Thin metallic films; Cold plasma reactor; ENGENHARIAS::ENGENHARIA ELETRICA::CIRCUITOS ELETRICOS, MAGNETICOS E ELETRONICOS; ENGENHARIAS::ENGENHARIA ELETRICA::ELETRONICA INDUSTRIAL, SISTEMAS E CONTROLES ELETRONICOS; ENGENHARIAS::ENGENHARIA ELETRICA::MATERIAIS ELETRICOS